Genetically encoded biosensors based on innovative scaffolds. (August 2020) - Moeyaert, Benjamien; Dedecker, Peter
Abstract: Genetically encoded biosensors are indispensable tools for visualizing the spatiotemporal dynamics of analytes or processes in living cells in vitro and in vivo. Their widespread adaptation has gone hand in hand with the development of sensors for new analytes or processes and improved functionality and robustness. In this review, we highlight some of the recent advances in genetically encoded biosensor development, with a special focus on novel and innovative scaffolds that will lead to new possibilities in the future.